Service-state behavior of reinforced soil walls supporting spread footings: a parametric study using finite-element analysis. Issue 3 (9th December 2015) - Ambauen, S.; Leshchinsky, B.; Xie, Y.; Rayamajhi, D.
Abstract : Reinforced soil has become a common means of retaining soil and supporting spread footings due to ease of construction and cost-efficiency. However, the behavior of these structures under service state conditions is inherently complex and dependent on the selection of design factors. Factors that govern design include earth pressures, settlements and reinforcement strains, but are not easily attained from closed form solutions. This study aims to provide insight into the complex behavior of reinforced soil walls surcharged by a discrete footing in context of these design factors, facilitating the development of a numerical model. A nonlinear elastic–plastic constitutive soil material model was calibrated to experimental plane strain test data, while the performance of a wall model was compared against full-scale laboratory testing of an identical geosynthetic-reinforced wall from prior literature, demonstrating satisfactory agreement. This agreement enabled a parametric study of the same wall model with a discrete spread footing evaluating the effects of reinforcement type and vertical spacing, footing location, footing dimensions, and toe restraint on lateral earth pressure distributions, wall deformations and reinforcement strains. The results of the study demonstrated that simplified consideration of only reinforcement type on service-state performance of reinforced walls neglects the effects of closely spaced reinforcements on behavior. Use of closely spaced reinforcements created increased earth pressures, but also reduced lateral displacement, footing settlements and reinforcement strains. Furthermore, it enabled achievement of equivalent service state criteria for footings located closer to the wall facing, potentially enabling increased right-of-way or reduced deck length when supporting a bridge superstructure.